Penguatan Kemampuan Komunikasi dan Gaya Bahasa Komentator Sepakbola pada Turnamen Silaturrahmi Unimal FC 2025 - Juni Ahyar; Ikramuddin; Iba Harliyana (Jurnal Solusi Masyarakat (JSM), 2026)
This study aims to describe and analyze the Language Style (Stylistic) used by commentators during football matches at the 2025 Unimal FC Silaturrahmi Tournament. The language style of the commentator in the context of sports shows its own uniqueness influenced by the speed of the game, the need to trigger the emotions of the spectator, and the persuasive function. This phenomenon is reflected in the choice of diction, intonation, and tempo of speech which tend to be fast and full of emphasis. This research uses a qualitative approach based on Stylistic studies. The research data was in the form of the verbal speech of the commentators which were collected through the audio-visual recording technique of the match and then copied in the form of a textual transcript. Data analysis is carried out through the process of heuristic reading to identify and classify the types of language styles, as well as hermeneutic reading to interpret the functions and meanings contained in the language style. The results of this study are expected to describe the variation of the dominant language styles and explain the function of these language styles (e.g., informative, expressive, or conative functions) in building the atmosphere of the match.